Parasite Killing of Leishmania (V) braziliensis by Standardized Propolis Extracts - Reboucas-Silva, Jessica; Celes, Fabiana S.; Lima, Jonilson Berlink; Barud, Hernane S. [UNESP]; Oliveira, Camila I. de; Berretta, Andresa A.; Borges, Valeria M. (Hindawi Ltd, 2017)
Treatments based on antimonials to cutaneous leishmaniasis (CL) entail a range of toxic side effects. Propolis, a natural compound widely used in traditional medical applications, exhibits a range of biological effects, including activity against infectious agents. The aim of this study was to test the potential leishmanicidal effects of different propolis extracts against Leishmania (Viannia) braziliensis promastigotes and intracellular amastigotes in vitro. Stationary-phase L. (V) braziliensis promastigotes were incubated with mediumalone or treated with dry, alcoholic, or glycolic propolis extract (10, 50, or 100 mu g/mL) for 96 h. Our data showed that all extracts exhibited a dose-dependent effect on the viability of L. (V) braziliensis promastigotes, while controlling the parasite burden inside infected macrophages. Dry propolis extract significantly modified the inflammatory profile of murine macrophages by downmodulating TGF-beta and IL-10 production, while upmodulating TNF-alpha All three types of propolis extractwere found to reduce nitric oxide and superoxide levels in activated L. braziliensis-infected macrophages. Altogether, our results showed that propolis extracts exhibited a leishmanicidal effect against both stages of L. (V) braziliensis. The low cell toxicity and efficient microbicidal effect of alcoholic or glycolic propolis extracts make them candidates to an additive treatment for cutaneous leishmaniasis.